Short Communication: Using Precast Units in Dome Structures: The Dome of Salah Al-Dean Mosque in Tulkarm, Palestine - Riyad A. Kareem Awad (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
This paper describes a new method in constructing domes which was actually used in the construction of Salah Al-Dean Alyoubi’s Mosque in Tulkarm, Palestine. The principles of this method, with proved efficiency, were derived from traditional methods of dome construction used in Islamic Architecture. The Utilization of reinforced concrete in dome construction had some drawbacks, especially in the necessity of form works that has the exact shape of the dome. This led to the development of the new proposed method. Precast concrete units were utilized, without the need for any framework. This paper describes this method after analyzing various methods of dome construction. The advantages and disadvantages of each method are also discussed.